Science Materials Development Through Ethnophotography for Cultural Literacy - Rohmane, Syaiful; Supangat, Supangat; Rosad, Ade (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to develop ethnophotography-based Natural and Social Sciences (IPAS) teaching materials that are valid, practical, and effective in enhancing the cultural literacy of elementary school students. The development process employed a modified Borg & Gall R&D model through stages of needs analysis, data collection, product design, expert validation, revision, limited trials, and effectiveness testing. The research was conducted with teachers and fifth-grade students at Tegal Besar Public Elementary School, East Ogan Komering Ulu Regency. Data were obtained through observations, interviews, questionnaires, and documentation, and analyzed using descriptive quantitative and qualitative methods. The results show that the developed teaching materials achieved a high level of validity with an average expert score of 94.3%. They were also found to be highly practical based on positive responses from teachers and students. Effectiveness testing demonstrated improvement in students’ cultural literacy with an N-gain score of 0.82 (high category). The interactive digital format supports student engagement and strengthens understanding of the sociocultural context of their local environment. Therefore, the ethnophotography-based teaching materials are feasible for instructional use and contribute to contextual learning aligned with the Independent Curriculum.